Notas para unha tematización da narrativa infantil e xuvenil galega (1975-1985) - Pena Presas, Montse (Madrygal. Revista de Estudios Gallegos, 2008)
This article tries to be the first approach to the topics, trends and motives that have inspired the texts of Galician children narrative between 1975 and 1985.The analysis of these works will allow us to dwell upon the different subjects that contemporary authors were interested in, as well as to detect any thematic lines and to note any possible future innovations. Similarly, guide lines for the arrangement of the different stages of these first years of narrative for the young and children are propored.